A study on effectiveness of performance appraisal at MUIS / Zulyazrie Abd Rasa - Abd Rasa, Zulyazrie (2009)
By definition, a performance appraisal is a formal evaluation of an employee's job performance. To conduct a formal performance appraisal, the manager must complete an evaluation document and conduct an oral review with the employee who is being evaluated. This process involves providing the employee with feedback regarding how well he or she is performing the essential functions of his or her job. Performance appraisals usually assess how well the employee executes job duties, overall efficiency, as well as the outcomes, or results, of his or her activities. In this research proposal, the organization that will be used is Majlis Ugama Islam Sabah, which is one of the government agencies in Sabah. It is located at Sembulan in Kota Kinabalu Sabah.